Microglial Morphometric Parameters Correlate With the Expression Level of IL-1β, and Allow Identifying Different Activated Morphotypes - Fernández-Arjona, María del Mar; Grondona, Jesús M.; Fernández-Llebrez, Pedro; López-Ávalos, María D. (Frontiers in Cellular Neuroscience, 2019)
Microglia are the resident macrophages in the brain. Traditionally, two forms of microglia have been described: one considered as a resting/surveillant state in which cells have a highly branched morphology, and another considered as an activated state in which they acquire a de-ramified or amoeboid form. However, many studies describe intermediate microglial morphologies which emerge during pathological processes. Since microglial form and function are closely related, it is of interest to correlate microglial morphology with the extent of its activation. To address this issue, we used a rat model of neuroinflammation consisting in a single injection of the enzyme neuraminidase (NA) within the lateral ventricle. Sections from NA-injected animals were co-immunolabeled with the microglial marker IBA1 and the cytokine IL-1β, which highlight features of the cell´s shape and inflammatory activation, respectively. Activated (IL-1β positive) microglial cells were sampled from the dorsal hypothalamus nearby the third ventricle. Images of single microglial cells were processed in two different ways to obtain 1) an accurate measure of the level of expression of IL-1β (indicating the degree of activation), and 2) a set of 15 morphological parameters to quantitatively and objectively describe the cell´s shape. A simple regression analysis revealed a dependence of most of the morphometric parameters on IL-1β expression, demonstrating that the morphology of microglial cells changes progressively with the degree of activation. Moreover, a hierarchical cluster analysis pointed out four different morphotypes of activated microglia, which are characterized not only by morphological parameters values, but also by specific IL-1β expression levels. Thus, these results demonstrate in an objective manner that the activation of microglial cells is a gradual process, and correlates with their morphological change. Even so, it is still possible to categorize activated cells according to their morphometric parameters, each category presenting a different activation degree. The physiological relevance of those activated morphotypes is an issue worth to be assessed in the future.